Serum thyroglobulin evaluation on LC-MS/MS and immunoassay in TgAb-positive patients with papillary thyroid carcinoma. Issue 1 (19th January 2022) - Nishihara, Eijun; Hobo, Yoshitaka; Miyauchi, Akira; Ito, Yasuhiro; Higuchi, Miyoko; Hirokawa, Mitsuyoshi; Ito, Mitsuru; Fukata, Shuji; Nishikawa, Mitsushige; Akamizu, Takashi
Abstract : Objective: This study aimed to elucidate disproportionately low serum thyroglobulin (Tg) values in Tg antibody (TgAb)-positive patients with structural recurrence of papillary thyroid carcinoma (PTC) using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Design: A retrospective study was performed on 176 patients in whom Tg and TgAb levels were measured between 2016 and 2021. Several comprehensive analyses of Tg-LC-MS/MS with an electrochemiluminescence immunoassay for Tg (Tg-ECLIA) were conducted using serum samples. Methods: TgAb-positive patients who underwent total thyroidectomy with multiple lung metastases due to PTC were evaluated using Tg-LC-MS/MS and Tg-ECLIA. Tg expression in lymph node metastases and metastatic lesions was evaluated by immunohistochemistry and Tg levels of aspiration washouts were also evaluated. Two in vitro assays were performed to elucidate TgAb interference. Results: Tg concentrations of negative TgAb in both assays were similar (R 2 = 0.99; n   = 52). Patients with structural recurrence showed higher Tg values with Tg-LC-MS/MS than with Tg-ECLIA. The undetectable proportion was significantly lower with Tg-LC-MS/MS (31.6%, 6/19) than with Tg-ECLIA (68.4%, 13/19; P   = 0.023). The spike-recovery rate and Tg concentrations determined by the serum mixture text ( n   = 29) were significantly reduced to 75.0% (118.3–88.7%) and 81.3% (107.0–87.0%), respectively, with TgAb using Tg-ECLIA (both P   < 0.001) confirming assay interference but not using Tg-LC-MS/MS (91.8–92.3%, P   = 0.77 and 98.4–100.8%, P   = 0.18, respectively). Conclusions: TgAb had no effect on the Tg-LC-MS/MS assay but yielded 19–25% lower values in Tg-ECLIA. Tg-LC-MS/MS is preferable for monitoring serum Tg levels in TgAb-positive patients, although those with structural recurrence often had disproportionally low Tg values.